NUTRIETIVE EVAULATION AND IN-SITU DIGESTIBILITY OF IRRIGATED GRASSES - M. N. Manzoor; J. I. Sultan; M. U. Nisa.; M. Q. Bilal (Journal of Animal and Plant Sciences, 2013)
The study aimed to determine the nutritive value of Cenchrus ciliaris, Leptochloa fusca, Chloris gayana, Cynodon dactylon and Panicum colunum grasses for ruminants. Five samples of each grass were taken and composite samples of each grass were oven dried at 55°C. Chemical analysis revealed that dry matter (DM) content varied from 11.38% (C. gayana) to 28.36% (C. dactylon). Maximum crude protein (11.3%) was observed for C. ciliaris while minimum (7.90%) was noted for P. colunum. Higher ash content (13.70%), hemicellulose (28.5%)and NDF (70.7%) contents were noted for C. dactylon. Gross energy value was optimum (3412.2 Kcal/kg) for C. gayana but minimum (2812.1 Kcal/kg) for L.fusca. The Ca, 1.6-4.0; P, 0.14-0.59; Mg, 0.26-0.84; Na, 5.0-10.5; and K, 11.6-27.2 g/kg of DM. However, Ca:P ratio varied from 4.55-16.36. Maximum in-situ DM digestibility (73.3%) and NDF digestibility (62.67%) were noted for C.ciliaris, while minimum in-situ DM digestibility (32.8%) and NDF digestibility (27.37%) were examined in L. fusca. Based on the findings of the present study, grasses as ruminant feed were ranked as C. ciliaris> C. dactylon> C. gayana> L. fusca> P. colunum
Keywords: evaluation; in situ; digestibility; grasses